How Does the Association between Social Support and Drug Court Completion Vary by Drug of Choice? - Parker, Mary Jane (2019)
Drug courts are a common way of handling drug-related cases in the criminal justice system, with the goal of treating the clients’ substance dependency and related criminal behavior. Despite their popularity and effectiveness, some clients are not successful in drug court. Therefore, to improve drug court and client success, this study examines how social support and drug of choice impact drug court completion and how drug of choice moderates the association between social support and drug court completion. Utilizing logistic regression to analyze data from three Indiana problem-solving courts that serve drug-involved offenders, this study finds mixed effects on how social support impacts drug court completion. Formal social support has a significant yet negative effect on completion, while informal social support does not have a significant effect on drug court completion. Furthermore, it finds that drug of choice is a significant predictor of drug court completion, and drug of choice also moderates the relationship between formal social support and drug court completion